A constructionist learning environment for teachers to model learning designs. (15th November 2011) - Laurillard, D.; Charlton, P.; Craft, B.; Dimakopoulos, D.; Ljubojevic, D.; Magoulas, G.; Masterman, E.; Pujadas, R.; Whitley, E.A.; Whittlestone, K.
Abstract The use of digital technologies is now widespread and increasing, but is not always optimized for effective learning. Teachers in higher education have little time or support to work on innovation and improvement of their teaching, which often means they simply replicate their current practice in a digital medium. This paper makes the case for a learning design support environment to support and scaffold teachers' engagement with and development of technology‐enhanced learning, based on user requirements and on pedagogic theory. To be able to adopt, adapt, and experiment with learning designs, teachers need a theory‐informed way of representing the critical characteristics of good pedagogy as they discover how to optimize learning technologies. This paper explains the design approach of the Learning Design Support Environment project, and how it aims to support teachers in achieving this goal.